On/ in the ground with Vietnamese communists: The Cu Chi Tunnels in the classroom - NGOEI, Wen-Qing (Institutional Knowledge at Singapore Management University, 2025)
Undergraduates often arrive in my classes convinced that great men, and a few exceptional women, are the ones who make history. Here, they think of power wielded by presidents, generals, and self-styled geniuses of strategy and diplomacy. (Henry Kissinger’s name invariably bubbles up in class discussions, like it or not.) Perhaps this happens elsewhere? In Singapore, this mindset likely takes root because the country’s record of benevolent authoritarianism underpins the legitimacy and influence of political elites. Equally, male citizens of Singapore perform compulsory military service before entering university and internalize, readily or grudgingly, that rank confers power—it is power—and that those of lower stations must fall in line. This is the lens through which many of my undergraduates initially viewed the Vietnam wars, certain that the conflict was orchestrated chiefly, even exclusively, by politico-military elites. Furthermore, those among my undergraduates who, in their middle or high school years, opted to study history probably absorbed from the national textbook that the Vietnam conflict was essentially a proxy war (though I know teachers take pains to emphasize nuances to this description contained within the same textbook). Hence, a fair number of my undergraduates will cursorily note that the struggle for Vietnam was local in some sense but resolve that the war was more properly an extension of the US-Soviet Cold War from Europe into Asia.1 Some are quick to even conclude that the big powers basically made puppets of the Vietnamese; indeed, they show little concern for the ground-level experiences of ordinary Vietnamese. From that vantage point, the Vietnam wars are a chess game played by powers at great remove from the board, or even a crater-riddled battlefield of tiny, faceless figures glimpsed as if from a high-altitude bomber.